Comparative cytogenetics of nine species of Hypoptopomatinae (Teleostei: Siluriformes: Loricariidae): The importance of structural rearrangements in chromosome evolution - Ferreira, Daniela Cristina [UNESP]; Chiachio, Márcio César [UNESP]; Takako, Adriana Kazue [UNESP]; Andreata, Artur Antonio [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Firenze University Press, 2005)
Fishes of the subfamily Hypoptopomatinae are very common and found in the lowlands of cis-Andean South America from Venezuela to the north of Argentina. With the main objective of contributing for a better understanding of the importance of chromosome rearrangements in the loricariid evolution, cytogenetic analyses were conducted in nine species of Hypoptopomatinae. The results showed a marked gross karyotypic conservation with the presence of 2n=54 chromosomes in all species analyzed. The main differences were found in the karyotypic formulae level. Most species had a single interstitial Ag-NORs, however terminal Ag-NORs were observed in three species. One species exhibited two Ag-NOR-bearing chromosome pairs. The distribution of C-band positive segments was species specific but chromosome markers were observed among the species analyzed. The gross cytogenetic characteristics observed among the Hypoptopomatinae species are similar to those observed in other primitive Loricariidae species suggesting that small changes, mainly paracentric and pericentric inversion were the main events in the karyotypic evolution of this fish group.
Keywords: Ag-NORs; C-band; Chromosome evolution; Fish cytogenetics; Karyotypes; Loricariidae; Pisces; Siluriformes; Teleostei